DIFFERENCES IN OCCUPATIONAL FACTORS AGAINST MUSCULOSKELETAL COMPLAINTS IN WORKERS WITH DIFFERENT TYPES OF VENTILATION - Zaenuri, Amalia Dwi Putri (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2024)
Background: Transport workers are one of the jobs in the informal sector. There is a tendency that the work of transportation workers does not have a good organizational system so that they do not think about occupational safety and health. Based on the results of a preliminary study, transport workers in market X and shop houses in market X complain of musculoskeletal complaints even though the two markets have different types of ventilation. Objective: analyze whether there are differences in occupational factors on musculoskeletal complaints in transport workers with different types of ventilation. Method: This research is a comparative descriptive study with 35 respondents each carrying laborers from the market with natural and artificial ventilation. The statistical test of the difference used was the Man-Whitney test because the data were not normally distributed. Conclusions: The results of Asymp. Sig. The 2-tailed variable for working period for musculoskeletal complaints is 0.617 while for the physical workload variable for musculoskeletal complaints it is 0.793. There is no difference between years of work and physical workload on musculoskeletal complaints in haul workers who work in the market with different types of ventilation